Signal and noise extraction from analog memory elements for neuromorphic computing - N. Gong (Nature Portfolio, 2018)
The application of resistive and phase-change memories in neuromorphic computation will require efficient methods to quantify device-to-device and switching variability. Here, the authors assess the impact of a broad range of device switching mechanisms using machine learning regression techniques.